Lessons from LIMK1 enzymology and their impact on inhibitor design. Issue 21 (5th November 2019) - Salah, Eidarus; Chatterjee, Deep; Beltrami, Alessandra; Tumber, Anthony; Preuss, Franziska; Canning, Peter; Chaikuad, Apirat; Knaus, Petra; Knapp, Stefan; Bullock, Alex N.; Mathea, Sebastian
Abstract: LIM domain kinase 1 (LIMK1) is a key regulator of actin dynamics. It is thereby a potential therapeutic target for the prevention of fragile X syndrome and amyotrophic lateral sclerosis. Herein, we use X-ray crystallography and activity assays to describe how LIMK1 accomplishes substrate specificity, to suggest a unique 'rock-and-poke' mechanism of catalysis and to explore the regulation of the kinase by activation loop phosphorylation. Based on these findings, a differential scanning fluorimetry assay and a RapidFire mass spectrometry activity assay were established, leading to the discovery and confirmation of a set of small-molecule LIMK1 inhibitors. Interestingly, several of the inhibitors were inactive towards the closely related isoform LIMK2. Finally, crystal structures of the LIMK1 kinase domain in complex with inhibitors (PF-477736 and staurosporine, respectively) are presented, providing insights into LIMK1 plasticity upon inhibitor binding.